1993
DOI: 10.1152/ajpheart.1993.265.1.h316
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of cardiac filling pressure on cardiac output during rest and dynamic exercise in dogs

Abstract: At rest, central venous pressure (CVP) falls when cardiac output (CO) rises. This can be attributed to flow-dependent redistribution of blood volume from central to peripheral blood vessels. In contrast, CVP rises during dynamic exercise despite a rise in CO. Therefore peripheral circulatory changes during exercise must counteract the factors that lower CVP when CO rises during rest. Our objectives were to determine the importance of blood flow, the muscle pump, and reflexes on changes in ventricular filling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
61
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 0 publications
5
61
0
Order By: Relevance
“…Komamura et al (20) demonstrated in dogs with pacing-induced HF that the failing ventricle is not able to increase SV in response to acute volume loads. In addition, in normal dogs, MMR activation causes substantial central blood volume mobilization (35), which maintains ventricular filling pressure that would otherwise decrease due to the rise in CO (43,45). In HF, this central blood volume mobilization still occurs, as evidenced by large increases in central venous pressure (11), but evidently even this increase in filling pressure is ineffective in raising CO during MMR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Komamura et al (20) demonstrated in dogs with pacing-induced HF that the failing ventricle is not able to increase SV in response to acute volume loads. In addition, in normal dogs, MMR activation causes substantial central blood volume mobilization (35), which maintains ventricular filling pressure that would otherwise decrease due to the rise in CO (43,45). In HF, this central blood volume mobilization still occurs, as evidenced by large increases in central venous pressure (11), but evidently even this increase in filling pressure is ineffective in raising CO during MMR activation.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent the HR responses cause changes in CO can be variable, as a result of reciprocal changes in SV (17,48), which can likely be attributed to the changes in ventricular filling time. Furthermore, even if SV is initially maintained, an increase in CO will decrease central venous pressure, thereby, decreasing right ventricular filling pressure, which would ultimately limit the ability to sustain left ventricular SV and, therefore, sustain the rise in CO (6,30,40). Because of the capacitance of the pulmonary circulation, the fall in the ventricular filling does take time to occur, and therefore, transient changes in HR can still cause transient changes in CO (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, we and others have observed that changes in HR do not necessarily elicit proportional changes in CO because stroke volume (SV) may also vary with the changes in ventricular filling time (17,34,48). Furthermore, transient increases in CO will lower ventricular filling pressure (and decreases in CO will raise filling pressure), thereby providing a self-limiting response (6,30,40). Furthermore, baroreflex control of HR may not functionally buffer high-frequency (Hi-F: above 0.15 Hz) blood pressure fluctuations (4,38,44).…”
mentioning
confidence: 99%
“…venous physiology; venous return; cardiac filling pressure THE DISTRIBUTION of cardiac output between compliant vasculature (e.g., splanchnic organs and skin) and noncompliant vasculature (e.g., skeletal muscle) is proposed to constitute an important determinant of the amount of blood available to the heart (e.g., central venous pressure, central blood volume) (6,13,16,17). The redistribution of cardiac output from compliant to noncompliant circulations is proposed to constitute a critical adjustment that permits cardiac output to increase in dynamic exercise (10,12,27,28), and redistribution of blood flow to the compliant skin circulation during heat stress is thought to reduce stroke volume and thereby impose a limitation on the ability to maintain or increase cardiac output in this setting (22). However, there is recent evidence against this idea (9); thus the concept remains controversial.…”
mentioning
confidence: 99%
“…Another approach has been to alter cardiac output distribution by evoking reflexes (8) or infusing drugs (16). The third approach has been to impose stresses that alter cardiac output distribution such as exercise (27,28) and combined exercise and heat stress (9,22). There are important limitations to each of these approaches.…”
mentioning
confidence: 99%